Factors contributing to the high prevalence of intimate partner violence among south Sudanese refugee women in Ethiopia - Filmawit Hadush; Dereje Tsegaye; Sherif Abdulwehab Legass; Endegena Abebe; Sabit Zenu (BMC, 2023)
Abstract Background Intimate partner violence is a universally occurring form of violence against women which is perpetrated by a husband or other intimate partner. It is a common public health problem during humanitarian crisis. Despite this, little is known about the problem among South Sudanese refugee women in Ethiopia. Objective This study aimed to determine the prevalence of intimate partner violence and identify its contributing factors among married refugee women in Pinyudo refugee camp, Gambella, Ethiopia in 2021. Methods A community-based cross-sectional study was conducted from March to June 2021. A random sample of 406 refugee women was included in the study. A structured, pretested, and interviewer-administered questionnaire was used to collect the data. Data were entered into epi-data version 3.1 and exported to SPSS version 22 for analysis. Multivariable logistic regression was run to identify factors associated with intimate partner violence. Statistical significance was affirmed using Adjusted Odds Ratio with its 95% Confidence Interval at a p-value ≤ 0.05. Results A total of 406 married refugee women participated in the study making a response rate of 96.2%. The overall prevalence of intimate partner violence in the past 12 months was 48.3% 95% CI= (43.6-53.2). Low-income contribution [AOR = 2.4, 95% CI: 1.2-5.5], and attitudinal acceptance [AOR = 2.1, 95%CI: 1.2-3.8] were significantly associated with the problem. Conclusion The prevalence of intimate partner violence is alarmingly high as half of participating women reported facing the problem in the year preceding the study. Low-income contribution and attitudinal acceptance were associated with a higher probability of experiencing violence. The government, humanitarian organizations, and other stakeholders should enable refugee women to generate income. There should be continuous women empowerment and behavioral interventions to improve refugee women's attitudes towards intimate partner violence.